59.9k views
0 votes
4x + 9 = -7x + 42 help

2 Answers

3 votes


{ \blue{ \boxed{ \pink{ \tt{x = 3}}}}}

Explanation:


{ \green{ \sf{4x + 9 = - 7x + 42}}}


{ \green{ \sf{4x + 7x = 42 - 9}}}


{ \green{ \sf{11x = 33}}}


{ \green{ \sf{x = (33)/(11)}}}


{ \boxed{ \blue{ \tt{x = 3}}}}

User Jasan
by
6.1k points
1 vote

The given expression is


4x+9=-7x+42

First, we add 7x on each side


\begin{gathered} 4x+7x+9=-7x+7x+42 \\ 11x+9=42 \end{gathered}

Second, we subtract 9 from each side


\begin{gathered} 11x+9-9=42-9 \\ 11x=33 \end{gathered}

At last, we divide the equation by 11.


\begin{gathered} (11x)/(11)=(33)/(11) \\ x=3 \end{gathered}

Hence, the solution is x = 3.

User PockeTiger
by
6.5k points